EVALUASI KEBIJAKAN BEROBAT GRATIS DI KABUPATEN TANJUNG JABUNG TIMUR PROPINSI JAMBI - Hendriyanto Julita Hendrartini Juanita (Center for Health Policy and Management, 2013)
Background: In the decentralized era, local government haswider authority to decide policies relevant with local needs.For this reason the Regent of Tanjung Jabung Timur District in2005 issued a decree on free medication at the health centerand secondary health center. However there are problemswith the sources and allocation of budget to support the decree.Besides, there is also a problem with target of the programfunded by the government. Therefore there should be anevaluation to find out facts for future improvement.Objective: The study aimed to identify mechanisms of funding,relevance of target and efficiency of the policy.Method: This was an explanatory case study which usedquantitative and qualitative approaches. Analysis units of thestudy were local government, health center and secondaryhealth center; and the subject were members of localparliament, head of health office, head of local planning council,head of health centers, staff of health centers/secondary healthcenters and the community. The size of samples to measuretarget relevance was determined using stratified sampling;qualitative method was determined using purposive sampling.Data were obtained through questionnaire, in-depth interviewand document checklist. Data were analyzed qualitatively andquantitatively in proportion.Result: Local government of Tanjung Jabung Timur allocatedbudget in the form of operational fund of health centers, drugallocation and incentives. The realization of budget was delayedso that health centers used alternative financial resources,i.e. budget of health insurance for poor community. Operationalfund did not give much support for free medication when therewas no clear cut distinction between users of health insurancefor poor communities and free medication. This caused overlapin budgeting which might end in inefficiency. The authority didnot do monitoring and supervision appropriately. Users of freemedication were mostly non poor communities. Poorcommunities utilized free medication at secondary healthcenters more frequently than at health centers.Conclusion: The local government of Tanjung Jabung TimurDistrict had not implemented good health insurance principlesin health financing to support free medication policies. Therewas misallocation of funding because more non – poorcommunities used the service. This increased the potential ofinefficiency in government budget utilization.Keywords: free medication policy, health financing, budgetefficiency